Using radio-telemetry to determine range and resource requirements of upland sandpipers at an experimentally managed prairie landscape - Mong, Tony Wayne (Kansas State University, 2005)
The native grasslands of North America are highly fragmented, and remaining tracts are intensively managed for grazing. Loss of tallgrass prairie and changing land management practices has caused many grassland birds that rely on these areas for breeding to decline in population numbers. To investigate resource selection and area use requirements of the upland sandpiper, we outfitted birds with radio transmitters at the experimentally managed Konza Prairie Biological Station in northeast Kansas. Two logistical challenges for wildlife telemetry projects are: minimizing the impact of radios on survival and movement, and optimizing the duration of transmitter attachment. We compared 4 methods of radio attachment for upland sandpipers under field conditions at breeding sites in tallgrass prairie. The daily probabilities of radio retention (DRR) for our 4 attachment methods were: 0.9992 (SE = 0.0005, n = 85) for a leg loop harness, 0.9801 (SE = 0.0099, n = 11) for radios glued to clipped feathers, 0.9627 (SE = 0.0085, n = 25) for radios glued directly to feathers and 0.8538 (SE = 0.0322, n = 20) for radios glued to plucked skin. The expected duration of radio attachment ranged from 1290 days for the leg loop harness, and 6 to 50 days for the glue attachment techniques. Survival rates of males (DSR = 0.9987, SE = 0.0009, n = 53) and females (DSR = 0.9988, SE = 0.0008, n = 71) were similar, and the probability of surviving the 90-day breeding season was about 0.90 in both sexes. We recommend attaching radios with glue to clipped feathers for short-term telemetry studies and a leg loop harness if longer retention is desired. The unique landscape of Konza Prairie allowed us to investigate specific tallgrass management strategies, and their impact on the range and habitat requirements of a bird that relies on the prairie for breeding. We found that upland sandpipers have large home ranges during the breeding season (male: = 199.0 ha ± 40.5 SE, n = 21, female: = 247.7 ha ± 51.7 SE, n = 23). Male home ranges were twice as large during brood-rearing ( = 200.8 ha ± 69.1 SE, n = 9) than during the nesting period ( = 67.02 ha ± 11.84 SE, n = 14, 1 = 5.14, P = 0.023). Upland sandpipers selected home range sites that had been burned the same spring (n = 44, ²3 = 31.65, P < 0.001), but did not show preference for certain habitat types within their home range ( ²3 = 1.49, P = 0.685). During brood rearing upland sandpipers used sites with higher percentages of bare ground, herbaceous and short woody vegetation, and low amounts of vegetative litter. Management strategies for the upland sandpiper should seek to preserve large contiguous tracts of tallgrass prairie that receive a heterogeneous mix of burning and grazing.
Keywords: Upland sandpiper; Retention rate; Compositional analysis; Resource selection; Utilization distribution; Biology, Ecology (0329)